2012
DOI: 10.1002/jcp.24172
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid derived from the fetal ovary initiates meiosis in mouse germ cells

Abstract: Meiotic initiation of germ cells at 13.5 dpc (days post-coitus) indicates female sex determination in mice. Recent studies reveal that mesonephroi-derived retinoic acid (RA) is the key signal for induction of meiosis. However, whether the mesonephroi is dispensable for meiosis is unclear and the role of the ovary in this meiotic process remains to be clarified. This study provides data that RA derived from fetal ovaries is sufficient to induce germ cell meiosis in a fetal ovary culture system. When fetal ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 59 publications
4
31
1
Order By: Relevance
“…We used a SYCP3 antibody to identify the chromosomal axial elements at meiosis prophase I, as described previously (Mu et al, 2013). Combined staining for SYCP1 and SYCP3 was used to determine whether SYCP1 disassembly occurred.…”
Section: Chromosome Spreads and Immunofluorescence Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a SYCP3 antibody to identify the chromosomal axial elements at meiosis prophase I, as described previously (Mu et al, 2013). Combined staining for SYCP1 and SYCP3 was used to determine whether SYCP1 disassembly occurred.…”
Section: Chromosome Spreads and Immunofluorescence Stainingmentioning
confidence: 99%
“…Western blot analyses were conducted as described previously (Mu et al, 2013). Briefly, total proteins were extracted in WIP (CellChip Beijing Biotechnology Company) according to the manufacturer's protocol.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Conversely, Mu et al [17] concluded that RA derived from the ovary is important for germ cell meiosis initiation and that the level of RA in the ovary influences the size of the primordial pool. Considering the importance of meiosis for female fertility, RA self-sufficiency may be a more reliable and conservative strategy than ovary dependence on another organ.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aldh1a2/1a3 -null ovaries show proper meiotic induction of female germ cells [Kumar et al, 2011]. Moreover, ALDH1A1 is expressed in germ cells of female mice from E12.5 to E15.5 [Mu et al, 2013], and the expression of the Aldh1a2 ortholog has been reported in human gonads [Childs et al, 2011] and other vertebrate species [Smith et al, 2008;Piprek et al, 2013]. Therefore, it remains unclear whether the anteriorposterior pattern of meiotic initiation is regulated by diffusible RA signals [Griswold et al, 2012] or by intrinsic factors such as the RA receptors [Gely-Pernot et al, 2012;Minkina et al, 2014;Ikami et al, 2015] and epigenetic regulators upstream of Stra8 , such as polycomb repressive complex 1 (PRC1) [Yokobayashi et al, 2013].…”
Section: Ra Signaling Triggers Meiotic Initiation Of Female Germ Cellmentioning
confidence: 99%